PENGARUH INFORMATION QUALITY, CUSTOMER EXPERIENCE, DAN RELATIONSHIP QUALITY TERHADAP SUSTAINABLE PURCHASE INTENTION - Nur Safitri; Elistia Elistia (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of perceived information quality, customer experience, and relationship quality on sustainable purchase intention. This type of research is descriptive causality research with a quantitative method approach through purposive sampling techniques with 170 respondents who have rented freezers from PT. Hutama Solusi Indonesia and are domiciled in the Jakarta, Bogor, Depok, Tangerang, Bekasi, and Bandung areas. Primary data analysis was carried out using the Structural Equation Model Partial Least Square (SEM-PLS) method. The results of this study show that relationship quality between companies and customers is formed because it is influenced by customer experience and perceived information quality. Furthermore, the increase in sustainable purchase intention is influenced by customer experience and relationship quality, but perceived information quality has not significantly impacted sustainable purchase intention. Thus, the findings of this study can be used to evaluate Hutama Solusi Indonesia, PT, and sustainably obtain relationship quality and sustainable purchase intention from the factors of customer experience, perceived information quality, and customer experience.